2003
DOI: 10.2337/diabetes.52.8.2175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epistatic Interaction Involved in Obesity Using the KK/Ta Mouse as a Type 2 Diabetes Model

Abstract: The KK/Ta strain serves as a suitable polygenic mouse model for the common form of type 2 diabetes associated with obesity in humans. Recently, we reported the susceptibility loci contributing to type 2 diabetes and related phenotypes in KK/Ta mice. In this study, we focused on expression in the kidneys and liver of KK/Ta and BALB/c mice using differential display (DD) PCR. Zn-␣ 2 glycoprotein-1 (Azgp1) mRNA levels were increased in the kidneys and liver in KK/Ta mice, and sequence analysis revealed a missense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 31 publications
5
49
0
Order By: Relevance
“…In addition, both DIGE proteomic analysis and western blotting indicated that ZAG production was significantly higher in the vitreous fluid from PDR patients compared with that from non-diabetic patients. We do not why ZAG levels are increased in the vitreous of diabetic patients with PDR, but it should be noted that hyperglycaemia has been involved in ZAG production [23], and gene expression of ZAG has been found to be upregulated in mice with diabetic nephropathy [24]. In addition, ZAG hinders cell proliferation and reduces Cdc2 expression (a rate-limiting step in cell cycle) [25] and may therefore be a reactive limiting factor for PDR progression.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, both DIGE proteomic analysis and western blotting indicated that ZAG production was significantly higher in the vitreous fluid from PDR patients compared with that from non-diabetic patients. We do not why ZAG levels are increased in the vitreous of diabetic patients with PDR, but it should be noted that hyperglycaemia has been involved in ZAG production [23], and gene expression of ZAG has been found to be upregulated in mice with diabetic nephropathy [24]. In addition, ZAG hinders cell proliferation and reduces Cdc2 expression (a rate-limiting step in cell cycle) [25] and may therefore be a reactive limiting factor for PDR progression.…”
Section: Discussionmentioning
confidence: 78%
“…Although its biological functions are incompletely understood, it seems to be a novel adipokine that may be involved in the local regulation of adipose tissue function [20][21][22][23]. ZAG has been recently identified by proteomic analysis in vitreous fluid from PDR patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…59 A single-nucleotide polymorphism in exon 2 of the ZAG gene was identified in KK/Ta mice and this polymorphism, a missense mutation at codon 24, may contribute to a type 2 diabetes-related phenotype involving obesity. 59 Further genetic evidence was provided by the demonstration that ZAG-knockout mice were susceptible to weight gain, particularly after a high-fat diet.…”
Section: Zag: a Candidate Gene For Obesitymentioning
confidence: 99%
“…59 A single-nucleotide polymorphism in exon 2 of the ZAG gene was identified in KK/Ta mice and this polymorphism, a missense mutation at codon 24, may contribute to a type 2 diabetes-related phenotype involving obesity. 59 Further genetic evidence was provided by the demonstration that ZAG-knockout mice were susceptible to weight gain, particularly after a high-fat diet. 60 This phenotype appears to be the result of reduced lipolytic responses to several stimuli, including isoprenaline, CL316243 (a b3-agonist), foskolin and isobutylmethylxanthine, in adipocytes.…”
Section: Zag: a Candidate Gene For Obesitymentioning
confidence: 99%
See 1 more Smart Citation